Perception, knowledge and attitude towards childhood fever: A survey among final‐year medical students. Issue 1 (24th August 2022) - Milani, Gregorio P.; Corsello, Antonio; Fadda, Marta; Falvo, Ilaria; Giannì, Maria Lorella; Marseglia, Gian Luigi; Cuppari, Caterina; Bruzzese, Eugenia; Bianchetti, Mario G.; Schulz, Peter J.; Peroni, Diego; Marchisio, Paola; et al.
Abstract : Aims: Undue concerns about the consequences of fever and its inappropriate management have been documented worldwide among physicians. However, no data exist on medical students. We investigated the perception, knowledge and attitude towards childhood fever among final‐year medical students. Methods: Between June and September 2021, final‐year medical students of six Italian universities were invited to complete an online survey on their conceptions and attitude towards pharmacological and non‐pharmacological management of childhood fever. History of relevant personal or second‐hand experience with childhood fever was also addressed. Both quantitative and qualitative approaches were used. Results: Of 1095 (69%) final‐year medical students, 756 completed the survey. Many students believe that high fever might cause brain damage, would recommend physical methods and alternate two drugs for fever. Most students do not think that fever has mainly beneficial effects. In Northern Italy, students are less likely to believe that fever might lead to brain damage (OR 0.55, 95% CI 0.33–0.94), and in Southern Italy students are more likely to advise physical methods (OR 1.77, 95% CI 1.22–2.57) and less likely to believe that fever has mainly beneficial effects (OR 0.55, 95% CI 0.39–0.77). History of a relevant personal episode of fever during childhood was not associated with these outcomes. Conclusions: Misconceptions about fever are common among final‐year medical students in Italy. Cultural factors rather than individually learned traits might underlie these beliefs. Medical students are a promising target for educational interventions to improve childhood fever management.